Evaluation of Oil and Gas Economy using Economics Profit Indicators and Prototype Macro VBA Excel - Juwairiah, Juwairiah; Indarwanta, Didik; Kodong, Frans Richard (RSF Conference Series: Engineering and Technology, 2022)
The oil and gas sector is an important factor in sustainable development, so it is considered necessary to make serious changes in conducting economic analysis on the oil and gas business. Oil and gas industry activities consist of upstream activities, and downstream activities. Activities in these upstream and downstream operations have high risk, high costs and high technology, so the company continuously tries to reduce the importance of the adverse impact of these risks on the work environment and people. Thus, evaluating the factors that affect sustainable production in this sector becomes a necessity. In this research will be evaluated the economy of the oil and gas field using methods of economic indicators, among others; NPV, POT, ROR, where these factors are estimated in order to be able to estimate the prospects of the oil and gas field so that the decision that the field development project can be implemented or cannot be taken immediately. Implementation of oil and gas field economic evaluation in this study using Macro VBA Excel. From several methods of economic analysis obtained that the results of this study show high precision compared to other methods, in addition to the way of evaluation using the above economic indicators is very popular.